Influence of mulching and plant spacing on growth and yield of french bean (Phaseolus vulgaris L.) (Progressive Agriculture, 2015)
A field experiment was conducted at the Horticulture Farm of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh to investigatethe effect of mulching and plant spacing on the growth and yield of French bean during the period from November 2014 to January 2015. The experiment consisted of three types of mulchingnamely (i) control (without mulch), (ii) water hyacinth and (iii) black ploythene much and three levels of spacing viz., (i) 30 cm x 25 cm (ii) 30 cm x 20 cm and (iii) 30 cm x 15 cm. The experiment was laid out in randomized complete block design with three replications. Results showed that both mulching and plant spacing significantly influenced the growth and yield components of French bean. Black polythene mulch produced the highest yield (5.82 t/ha) and the lowest yield (4.92 t/ha) was recorded fromno mulch treatment. The maximum yield (6.22 t/ha) was obtained from 30 cm x 15 cm plant spacing and the lowest (4.58 t/ha) was obtained with 30 cm x 25 cm plant spacing. The combined effects of mulching and plant spacing were statistically significant. The combination of black polythene mulch with 30 cm x 15 cm spacing gave the highest yield (6.97 t/ha) and the lowest yield (3.94 t/ha) was received from without mulching at spacing of 30 cm x 25 cm treatment combination. Considering the above findings the black polythene mulch with 30 x 15 cm plant spacing  may be recommendfor French bean cultivation.Progressive Agriculture 26 (2): 129-135, 2015